ANALISIS PENGARUH ETHICAL LEADERSHIP TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN PSYCHOLOGICAL WELL-BEING SEBAGAI VARIABEL MEDIASI (Studi pada Karyawan Bank Syariah di Semarang) - Aji, Bagas Ananta; Andriyani, Andriyani (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to analyze the effect of ethical leadership on organizational citizenship behavior with psychological well-being as a mediating variable. This research consists of three variables, namely one independent variable, one dependent variable, and one mediating variable. The independent variable in this study is ethical leadership. The dependent variable in this study is organizational citizenship behavior. Meanwhile, the mediating variable in this study is psychological well-being. The sample was selected using the census method, so the entire population is used as research respondents. Data was collected by sending an online questionnaire to the frontliner employees of Bank Syariah in Semarang. A total 46 respondents participated in this studies. Data analysis was performed using Partial Least Square analysis through the SmartPLS 3 program. The results of this study indicate that ethical leadership has a positive and significant effect on organizational citizenship behavior. The results of this study also show that psychological well-being significantly mediates the indirect effect between ethical leadership and organizational citizenship behavior